PERANCANGAN SISTEM PENDETEKSI BERITA HOAX MENGGUNAKAN ALGORITMA LEVENSHTEIN DISTANCE BERBASIS PHP - Aprillianda Pasaribu; Marto Sihombing; Relita Buaton (STMIK KAPUTAMA, 2020)
In the 4.0 era where the Internet is an important part of life today, information can be easily accessed anytime, anywhere. But not all information distributed through the internet is in the form of facts. Data presented by the Ministry of Communication and Information based on a survey conducted in 2018 said that as many as 800,000 sites in Indonesia indicated that non-fact or hoax news spreaders were indicated. As a result of hoax news generated is very dangerous because it attacks the minds of the human subconscious, so it is needed a system that can detect hoax news. In this study used a database containing hoax news documents. The algorithm applied is the TF-IDF algorithm to measure the weight of a word in a hoax document and combined with the Levenshtein Distance (LD) algorithm to measure the distance between words in a document. The application of the Levenshtein Distance Method in the Hoax Detection System has several stages that begin with the pre-processing of the word (prepocessing text) followed by the TF-IDF calculation phase and then the minimum distance calculation between words using the Levenshtein Distance algorithm. The result of a limit of 0.1 on 40 documents that have been classified as test data has high Precision, Recall and Accuracy values, namely Precision 1; Recall 0.71; and Accuracy 80%.